Intellectual Assets, CSR, and Innovation Performance of MSMEs in Bandung Regency - Mayanti, Yuni; Mintarsih, Mimin; Indraswari, Nurul Myristica (LifeSciFi, 2025)
Innovation is essential for the survival and growth of Micro, Small, and Medium Enterprises (MSMEs) amid global competition, particularly in Bandung Regency, a center of the creative economy in West Java. This study aims to analyze the role of intellectual assets and Corporate Social Responsibility (CSR) in enhancing MSME innovation performance. A qualitative descriptive method was applied through observations and interviews with ten MSMEs of varying scales. The findings reveal that intellectual assets comprising human, structural, and relational capital serve as primary drivers of innovation. Human capital stimulates creativity through knowledge and skills, structural capital ensures organizational support for continuous innovation, and relational capital facilitates collaboration with stakeholders. Integrating intellectual assets with CSR practices strengthens social legitimacy and fosters sustainable innovation aligned with the triple bottom line (people, planet, profit). CSR implementation not only improves corporate image but also promotes eco-innovation, cost efficiency, and product differentiation. The study concludes that the synergy between intellectual assets and CSR generates a unique, hard-to-imitate competitive advantage, shifting MSME innovation orientation from mere profit toward socio-environmental sustainability. These findings emphasize that strategic management of intellectual capital and CSR can serve as a foundation for MSMEs to compete in national and global markets.